Bridging animal and human models of exercise-induced brain plasticity - Voss, Michelle W. (Trends Cogn Sci, 2013)
Significant progress has been made in understanding the neurobiological mechanisms through which exercise protects and restores the brain. In this feature review, we integrate animal and human research, examining physical activity effects across multiple levels of description (neurons up to inter-regional pathways). We evaluate the influence of exercise on hippocampal structure and function, addressing common themes such as spatial memory and pattern separation, brain structure and plasticity, neurotrophic factors, and vasculature. Areas of research focused more within species, such as hippocampal neurogenesis in rodents, also provide crucial insight into the protective role of physical activity. Overall, converging evidence suggests exercise benefits brain function and cognition across the mammalian lifespan, which may translate into reduced risk for Alzheimer’s disease (AD) in humans.